In vivo Microscale Measurements of Light and Photosynthesis during Coral Bleaching: Evidence for the Optical Feedback Loop? - Wangpraseurt, Daniel; Holm, Jacob B.; Larkum, Anthony W. D.; Pernice, Mathieu; Ralph, Peter J.; Suggett, David J.; Kühl, Michael (Frontiers in Microbiology, 2017)
Climate change-related coral bleaching, i.e. the visible loss of zooxanthellae from the coral host, is increasing in frequency and extent and presents a major threat to coral reefs globally. Coral bleaching has been proposed to involve accelerating light stress of their microalgal endosymbionts via a positive feedback loop of photodamage, symbiont expulsion and excess in vivo light exposure. To test this hypothesis, we used light and O2 microsensors to characterise in vivo light exposure and photosynthesis of Symbiodinium during a thermal stress experiment. We created tissue areas with different densities of Symbiodinium cells in order to understand the optical properties and light microenvironment of corals during bleaching. Our results showed that in bleached Pocillopora damicornis corals, Symbiodinium light exposure was up to 5-fold enhanced relative to healthy corals, and the relationship between symbiont loss and light enhancement was well described by a power-law function. Cell-specific rates of Symbiodinium gross photosynthesis and light respiration were enhanced in bleached P. damicornis compared to healthy corals, while areal rates of net photosynthesis decreased. Symbiodinium light exposure in Favites sp. revealed the presence of low light microniches in bleached coral tissues, suggesting that light scattering in thick coral tissues can enable photoprotection of cryptic symbionts. Our study provides evidence for the acceleration of in vivo light exposure during coral bleaching but this optical feedback mechanism differs between coral hosts. Enhanced photosynthesis in relation to accelerating light exposure shows that coral microscale optics exerts a key role on coral photophysiology and the subsequent degree of radiative stress during coral bleaching.